REC Method in Comparison of Soundness Level of Islamic Bank in Indonesia and Malaysia - Putri, Sefti Nur Cahya; Risyanto, Havid; Suganda, Asep Dadan; Husni, En. Muhamad (Economica: Jurnal Ekonomi Islam, 2021)
This study analyzed the health of Islamic banking in Indonesia and Malaysia by using the REC approach. Through the quantitative descriptive method, this study collected data from official websites such as Bank Indonesia, the Financial Service Authority, and Bank Negara Malaysia. To determine the sample, purposive sampling with convenience sampling was done on 12 Islamic Commercial Banks in Indonesia and Malaysia. The risk profile is represented by the FDR ratio. It indicates significant differences in the soundness level of Islamic banks in Indonesia and Malaysia. Earning approach is represented by the ROA suggesting no significant difference in the soundness level of Islamic banking in Indonesia and Malaysia. For the capital approach represented by the CAR ratio, the results show that there is no significant difference in the soundness of Islamic banking in Indonesia and Malaysia. Simultaneously, the REC approach proves that there is no significant difference in the soundness of Islamic banking in Indonesia and Malaysia.